Validação do Balanço de Energia do Modelo Agro-Ibis para Soja em Duas Regiões do Brasil - Webler, Geovane; Moreira, Virnei; Timm, Andrea; Roberti, Débora Regina; Senna, Julio; Cuadra, Santiago Vianna (Ciência e Natura, 2011)
.